Determination of Lutein and Zeaxanthin Esters and Their Geometric Isomers in Carotenoid Ester Concentrates Used as Ingredients in Nutritional Supplements: Validation of a Combined Spectrophotometric-HPLC Method. (27th November 2019) - Lombeida, Wagner O; Rubio, Fernando; Levy, Luis W
Abstract: A combined spectrophotometric-LC method is described for the determination of total lutein and zeaxanthin ester content in carotenoid ester concentrates, including their main geometrical isomers. The concept of composite-specific absorbance is introduced for this purpose. The method is applicable to carotenoid ester concentrates used as ingredients in oil suspensions and dosage forms. The sample is dissolved in a hexane–2-propanol mixture (95 + 5, v/v) for spectrophotometric measurement at a maximum absorption of ~445 nm. Subsequently, in parallel, a sample is saponified and chromatographed on a normal-phase HPLC column to determine the relative percentage profile of the main geometrical isomers of both carotenoid esters. This, in turn, is used to calculate the composite-specific absorbance of the sample for the final calculation of results. The method, which solely uses reference standards to validate chromatographic conditions, avoids the common error of applying the specific absorbance of only the trans isomer for the calculation of total carotenoid content when cis isomers are present.